Wilson's Disease; Clinical Presentations among Patients Attending Gastroenterology Clinic/ Baghdad Teaching Hospital - . Mohammed, Ahmed Kh; Najeeb, Akram Ajeel; Tawfeeq, Wafaa Faeq (AL-Kindy College Medical Journal, 2013)
Background:Wilson’s disease (WD) is an inheriteddisorder of copper metabolism that is characterizedby tremendous variation in the clinical presentation.Objective: To assess demographic distribution,clinical presentations, diagnostic evaluation, and anyassociation between clinical presentations and otherstudied variables of a sample of Iraqi patients withWD.Methods: A descriptive cross sectional study withanalytic elements was conducted during 2011, fromthe 1st of February till the 10th of June. The samplingmethod was a convenient non-random one, carriedout through consecutive pooling of registered WDpatients. A questionnaire-form paper had beendeveloped for the process of data collection.Results: The study had enrolled 29 patients, with amale to female ratio of (1.07:1), their mean age was27.12±12.18 years. 82.8% of them lived in urbanarea. 48.3% were singles. Only 20.7% of patients hada positive family history of WD. 69% of patients hadconsanguineous parents. The main initial clinicalpresentations were; hepato-neurologic (31%), purehepatic (27.6%), neuro-psychiatric (13.8%) and otherpresentations (27.6%). Hepatic manifestations wereseen in (82.8%) of patients; jaundice was the mostfrequent (89.7%). Ophthalmologic manifestations in(55.1%) of patients including; Kayser-Fleischer rings(51.7%), diplopia (6.9%) and cataracts (3.4%).Neurologic manifestations existed in 44.8% ofpatients; tremors were the most frequent (41.4%).Psychiatric manifestations existed in 31% of patients;depression was the commonest (27.6%). Jointsmanifestations existed in 20.7% of patients. Thediagnosis delay was 11.26±8.2 months.Conclusion: The higher percentage of patients wereof hepato-neurologic and pure hepatic presentations.Patients with hepato-neurologic type are diagnosed inolder age, while those with neuro-psychiatric type arediagnosed in younger age and with longer diagnosisdelay.